Pengaruh Earning Per Share Terhadap Harga Saham Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2018 - Mantik, Mikha Q. H. M.; Tampi, Dolina L.; Manoppo, Wilfried S. (Sam Ratulangi University, 2019)
This research aims to test the partially influence, direction, and the significance of EPS against stock prices in the sector of consumer goods manufacturing company listed in IDX 2015-2018 Period. Financial information functions as a means of information, management accountability tool to the owner of the company, success indicators against the depiction of the company and as a material consideration in decision making. One of the indicators measuring share price i.e.: Earning Per Share. Earnings Per Share (EPS) to measure the company's ability to generate profits per shares. And the stock price is the closing price of the stock market during the period of observation for each type of stock. This research method is associative causal. Of the total population, conducted the withdrawal of samples as many as 29 companies with purposive sampling method, a sampling method that takes an object with certain criteria. Data analysis was done of simple linear regression analysis and hypothesis testing using the analysis of the coefficient of determination and test results showed t. EPS positive and significant effect against the price of the shares, with a value of the coefficient of determination (R 2) 0.435 and value 0.000 probability less than 0.05. Based on the results of test data analysis research, it can be seen that the level of variable earnings per shares or Earning Per Share (EPS) have a positive influence significantly to stock prices in the sector of consumer goods manufacturing company in Indonesia Stock Exchange.